Building peace through mystic philosophy: study on the role of Sunan Kalijaga in Java - Waston Waston (Indonesian Journal of Islam and Muslim Societies, 2018)
This paper aims to study the teachings of peace invented in the Javanese tradition particularly by Sunan Kalijaga. Sunan Kalijaga was a Muslim saint in the 15th century AD who taught mystical-philosophical teachings. His role permeates in the Javanese tradition so peaceful values that are embedded in its teachings still be traced and developed. We conducted a literature study on the role, influence and legacy of Sunan Kalijaga. We focused on his philosophical approach to religious thought as oppose to the mystical aspect. Our findings show that Sunan Kalijaga succeeded in using proper choice of words to combine Islamic values and predominant cultural elements (e.g., Hinduism, Buddhism). Therefore, instead of using the Arabic terms, Sunan Kalijaga used many old Javanese and Sanskrit terms commonly used in the 15th-16th century Javanese society. As an implication, Sunan Kalijaga created terms that are less Islamic but loaded with Islamic values. His examination is not only inherited into terms, but also practices, symbols and institutions. Among those Javanese traditions, some of them are critically important in supporting peace-building. This paper reaps the peaceful values of the Sunan teachings in the hope of countering the stream of extreme ideologies that have recently flooded the public. Paper ini bertujuan mengunduh ajaran damai yang ditanam dalam tradisi Jawaterutama yang disemai oleh Sunan Kalijaga. Sunan Kalijaga adalah seorang walipada abad ke 15 M yang memiliki ajaran bersifat mistis-filosofis. Hingga saat ini,pengaruh Sunan Kalijaga sangat terasa dalam tradisi Jawa sehingga nilai-nilaidamai yang ada dalam ajarannya masih dapat ditelusuri dan dikembangkan.Dengan menerapkan studi pustaka, data-data dalam riset ini dikumpulkan darisumber-sumber yang mengkaji Sunan Kalijaga, peran, pengaruh, dan warisanwarisannya.Oleh karena corak pemikiran keagamaan Sunan Kalijaga bersifatmistis-filosofis, maka aspek mistisisme dan pendekatan filsafat juga digunakandalam tulisan ini. Paper ini memaparkan temuan bahwa dalam pratiknya, SunanKalijaga melakukan permainan bahasa yang dengan cara tersebut ia berhasilmemadukan antara nilai-nila i keislaman dengan unsur buda y a dominanyang telah ada sebelumnya yaitu Hindu dan Buddha. Oleh karena itu, alihalihmenggunakan istilah Arab, Sunan Kalijaga justru banyak menggunakanistilah Jawa Kuna dan Sansekerta yang lazim digunakan dalam masyarakat Jawaabad 15-16. Hasil dari upaya tersebut, Sunan Kalijaga menghadirkan istilahistilahyang tampaknya kurang Islami namun sarat muatan nilai-nilai Islam.Ijtihad Sunan Kalijaga tidak hanya terwariskan menjadi istilah-istilah, namunjuga menjadi praktik, simbol bahkan melembaga. Dari beberapa bentuk tradisijawa yang diwariskan Sunan Kalijaga dapat diambil bebera p a nilai pentingyang mendukung iklim damai. Paper ini memetik nilai-nilai damai ajaran sangSunan tersebut dengan harapan dapat membendung arus ideologi ekstrim yangakhir-akhir ini semakin membanjiri ruang publik.